Circulating tumor cells PD‐L1 expression detection and correlation of therapeutic efficacy of immune checkpoint inhibition in advanced non‐small‐cell lung cancer. Issue 5 (11th January 2023) - Zhou, Qing; Liu, Xiangning; Li, Ji; Tong, Bing; Xu, Yan; Chen, Minjiang; Liu, Xiaoyan; Gao, Xiaoxing; Shi, Yuequan; Zhao, Jing; Zhong, Wei; Wang, Mengzhao
Abstract: Introduction: This study investigated whether programmed death‐ligand 1 (PD‐L1) expression of circulating tumor cells (CTCs) in peripheral blood can serve as a predictive biomarker for immunotherapy efficacy in patients with advanced non‐small‐cell lung cancer (NSCLC). Methods: We employed a negative enrichment method to isolate CTCs. We identified PD‐L1 + CTCs as PD‐L1+/4′, 6‐diamidino‐2‐phenylindole (DAPI)+/CD45‐circulating tumor cells through an immunofluorescence method. Tumor tissue PD‐L1 expression was determined by immunohistochemical staining. The correlation between CTC PD‐L1 expression and patients' prognostic features was estimated through the Kaplan–Meier method. Results: CTCs released a higher detection rate of PD‐L1 expression than tumor tissues (53.0% vs. 42.1%). No correlation was observed between them. Forty‐nine NSCLC patients received anti‐PD‐1/PD‐L1 immunotherapy (three with combined anti‐PD‐1/PD‐L1 and cytotoxic T lymphocyte‐associated antigen‐4 (CTLA‐4), two with four cycles of combined immune checkpoint inhibitors [ICIs] plus chemotherapy and ICI monotherapy for maintenance). Patients with PD‐L1 expression on tissue or CTCs had a median progression‐free survival (mPFS) of 5.6 months ( n = 36, 95% confidence interval [CI] 3.6–7.5 months), significantly longer than those without PD‐L1 detection ( n = 9, mPFS of 1.4 months, 95% CI 1.3–1.5 months, log‐rank p = 0.032). The multivariable Cox proportional‐hazard model suggested that the tissue or CTC PD‐L1 expression was associated with a lower risk of progression (hazard ratio 0.45, 95% CI 0.21–0.98, p = 0.043). Conclusions: CTCs and tumor tissues reveal heterogeneous expression of PD‐L1 in NSCLC patients. Patients with baseline PD‐L1 expression on CTCs or tissue showed prolonged mPFS and may help to identify the subsets of patients who potentially benefit from immunotherapy. Abstract : To investigate whether programmed death‐ligand 1 (PD‐L1) expression of circulating tumor cells (CTCs) is associated with immunotherapy efficacy in non‐small‐cell lung cancer patients, we isolated CTCs based on a negative enrichment method and detected their PD‐L1 expression status. Patients with PD‐L1 + on tissue or CTCs released a significantly prolonged mPFS compared with those without PD‐L1 expression (5.6 months vs. 1.4 months; log‐rank p = 0.032).